Public Anthropology and the Academic Labor Movement: Lessons from the 2011 Wisconsin Uprising. (28th October 2015) - Pearson, Thomas W.
Abstract: Collective bargaining rights for University of Wisconsin (UW) faculty were eliminated as part of budgetary reforms that sparked widespread protests in early 2011 known as the Wisconsin Uprising. Despite losing these rights, faculty at some UW institutions have sought to maintain informal unions. My goal in reflecting on this effort is to examine the role of an engaged or public anthropology in the academic workplace. Over the past few decades, deep budget cuts, corporate managerial styles, and the casualization of academic labor have transformed higher education. Recent calls for anthropology to increase its relevance through public engagement with current issues, however, have largely ignored the political economy of academia and our participation as workers in labor movements.